Operational Risk Analysis of kWh Addition Services Using the RCA (Root Cause Analysis) Method at PT XYZ - Annisa Maudi Syafitri; Dira Ernawati (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Demand for additional electric power increases as electricity demand increases, but the process is often hampered by obstacles in the operational workflow. The main objective of this research is to analyze operational risks in kWh addition services using the Root Cause Analysis (RCA) method using the 5 Why technique and fishbone diagram. The RCA method equipped with a fishbone diagram will produce a mapping of the causes of operational risk obstacles in the PT XYZ kWh addition service in a structured manner. In the process, the author identifies and analyzes the various risks faced, and proposes improvements aimed at improving service quality. Based on the results of the research analysis, there are two operational risks related to kWh addition, namely: the migration process of postpaid kWh meters to prepaid meters and the use of electricity by customers who exceed the contracted power. The conclusion shows that most of the operational risks come from customer behavior. Proposed improvements include increasing the frequency of inspections, proactive planning for power additions, and transparency of information to customers. The results of this report are expected to make a positive contribution to operational risk management at PT XYZ and improve customer satisfaction.